Inspector Ellis. [Series 1] [videorecording (DVD)]. - Clarke, Sharon D.; Gower, Andrew, 1989-; Harding, Allison (Acorn TV, 2025)
DCI Ellis is a formidable cop who takes over the most challenging unsolved cases across Northwest England. Armed with integrity and razor-sharp instincts, Ellis steps in with unyielding determination as the last hope for failing investigations. Her unflappable demeanor disguises a deep-seated compassion for the victims, fueled by her complicated past. Amidst lies, secrets, and neglect, Ellis seeks justice for victims and truth for survivors.